Semi-analytical solution of frost heave force for circular tunnels in strain-softening rock mass - Shi, Linpo; Xing, Meng; Wang, Pengyu; Wang, Kai; Cao, Xiaowei; Liu, Hui (Frontiers in Earth Science, 2025)
The freezing method is often adopted to reinforce the surrounding formation during deep foundation pit excavations. According to the traditional theory of freezing wall design in coal mine construction engineering, it is necessary to design a continuous, thicker freezing wall. The multi-turn combination cylinder freezing wall structure can optimize the freezing design, but the strength and stability of the wall structure are theoretical and technical issues that urgently need to be researched and solved. In this work, the mechanical characteristics of frozen walls of multi-coil composite cylinders are analyzed using theoretical methods. Based on the elastoplastic theory, the freezing wall of a multi-turn combined cylinder is simplified to an axisymmetric plane problem, and the theoretical calculation model of the freezing expansion force, generated by the freezing process, around the perimeter of a circular hole under an axisymmetric plane strain model is developed. The corresponding variable model for the displacement immobility point of the freezing circle is proposed, and the progressive formation of the freezing wall is achieved through iterative calculations. The theoretical calculation formulas for the freezing force generated by the freezing process around a circular hole under the plane strain model are derived considering the gradual formation process of freezing expansion. The results of the research provide the theoretical basis for the construction of permafrost deep foundation pit engineering.